Reservoir Forming Dynamics of Differential Accumulation of Tight Oil in the Yanchang Formation Chang 8 Member in the Longdong Area, Ordos Basin, Central China - Yang, Jingru; Liu, Xianyang; Xu, Wanglin (Frontiers in Earth Science, 2022)
Tight oil is usually accumulated near source rocks after short-distance migration. For the Chang 8 tight oil reservoir in the Longdong area of the Ordos Basin, however, the tight oil accumulation does not completely follow the source control theory which points out that richer tight oil is found in zones closer to the source rock. The causes behind such differential accumulation need to be further analyzed. On the basis of previous studies, this paper accurately restored the oil migration dynamics in the main reservoir-forming period by using the latest paleo-hydrodynamic restoration technology through mudstone compaction analysis. Then, the oil migration dynamics were compared with the start-up pressure gradient of the transport layer along the potential oil migration path in the main reservoir-forming period. Finally, combined with the paleo-structural characteristics in the main reservoir-forming period, the causes for the differential accumulation of tight oil in Chang 8 Member of the Longdong area were analyzed. The study results show that (1) in the main reservoir-forming period, tight oil in Chang 8 Member tended to and could migrate from north and northeast to southwest and accumulate in the nose-like paleo-structure in the southwest; and (2) after the main reservoir-forming period, as the reservoir formation was compacted and the fluid pressure and hydrocarbon generation capacity reduced, oil accumulated near the source rock to a less extent than in the reservoir-forming period. In these two stages, changes in intensity of oil migration dynamics dominated the differential accumulation of tight oil. This study provides a new perspective for similar efforts.